2013
DOI: 10.1242/jeb.093294
|View full text |Cite
|
Sign up to set email alerts
|

The simple ears of noctuoid moths are tuned to the calls of their sympatric bat community

Abstract: SUMMARYInsects with bat-detecting ears are ideal animals for investigating sensory system adaptations to predator cues. Noctuid moths have two auditory receptors (A1 and A2) sensitive to the ultrasonic echolocation calls of insectivorous bats. Larger moths are detected at greater distances by bats than smaller moths. Larger moths also have lower A1 best thresholds, allowing them to detect bats at greater distances and possibly compensating for their increased conspicuousness. Interestingly, the sound frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…A frequently cited but untested hypothesis for the neural basis of evasive flight in noctuid moths is that the more sensitive receptor (A1) triggers directional flight, whereas the less sensitive receptor (A2) triggers last-ditch behaviour (Roeder, 1974b). This hypothesis implies that A1 and A2 encode different types of information about predation risk: potentially 'I am not yet detected by the bat' and 'I am now detectable by the bat' (ter Hofstede et al, 2013). Other authors (Surlykke, 1984;Ratcliffe et al, 2009) have suggested that A2 might only increase the dynamic range of the ear, i.e.…”
Section: Box 2 Neural Basis For Evasive Flight In Mothsmentioning
confidence: 99%
See 3 more Smart Citations
“…A frequently cited but untested hypothesis for the neural basis of evasive flight in noctuid moths is that the more sensitive receptor (A1) triggers directional flight, whereas the less sensitive receptor (A2) triggers last-ditch behaviour (Roeder, 1974b). This hypothesis implies that A1 and A2 encode different types of information about predation risk: potentially 'I am not yet detected by the bat' and 'I am now detectable by the bat' (ter Hofstede et al, 2013). Other authors (Surlykke, 1984;Ratcliffe et al, 2009) have suggested that A2 might only increase the dynamic range of the ear, i.e.…”
Section: Box 2 Neural Basis For Evasive Flight In Mothsmentioning
confidence: 99%
“…Larger moths, however, have more sensitive ears and detect bats at greater distances than do smaller moths, essentially compensating for their increased conspicuousness. This relationship between size and sensitivity is strongest for frequencies that are used by a large number of sympatric bats for echolocation (ter Hofstede et al, 2013). Forrest et al (1995) suggest that this pattern of size and sensitivity may apply across all insects with bat-detecting ears.…”
Section: Moth Species Sizementioning
confidence: 99%
See 2 more Smart Citations
“…A further common feature of all moth ears is that, given the few receptor cells present, moths cannot discriminate frequencies. Nevertheless, the ears might be tuned to a "best frequency" (Hofstede et al, 2013). However, other anatomical details, i.e.…”
Section: The Tympanic Ear Of Mothsmentioning
confidence: 99%